Temperaturas Superficiais de Frangos de Corte Alimentados com Níveis Crescentes de Glicerina Purificada. - Jorge, Maria Paula Balduino (Universidade Federal do Tocantins, 2023)
The objective of this study was to evaluate the surface temperature of broilers fed with increasing levels of glycerin purified from 1 to 21 days of age. A total of 240 male one-day-old Cobb 500 line broilers were used, with a mean initial weight of 48 ± 2.46 g, distributed in a completely randomized experimental design with four treatments (0, 2, 4 and 6% inclusion of purified glycerin) and six replicates of ten birds per experimental unit. The maximum, minimum, thermal amplitude and daily consumption of broilers from 7 to 21 days of age were evaluated in the 24-hour period. There was no interaction between the levels of inclusion of purified glycerin in the diets for maximum, minimum and thermal amplitude in the morning and afternoon, however, the maximum and minimum temperatures were influenced by the period, with no effect on the thermal amplitude. The increasing levels of glycerin purified in the diets did not influence the feed intake of the birds during the period from 10:00 am to 7:00 p.m., however, there was an effect on feed consumption from 7:00 p.m. to 7:00 p.m., where the birds fed with purified glycerin presented higher consumption when compared to the birds of the control group. It was concluded that the levels of up to 6% inclusion of purified glycerin in the diets did not influence the surface temperatures and the daily consumption of broiler chicken in the period from 1 to 21 days of age.